A facile method of synthesizing ammonia modified graphene oxide for efficient removal of uranyl ions from aqueous medium. Issue 94 (14th October 2015) - Verma, Swati; Dutta, Raj Kumar
<x xml:space="preserve">Abstract</x> Adsorption of uranyl ions on NH3 modified graphene oxide at pH 6.